Great debates : ciminal law - "Herring, Jonathan" (Hampshire, 2009)
An engaging introduction to some of the more advanced writing on criminal law for a reader with a reasonable grasp of the basic legal principles, illuminated throughout with discussion of the specific issues which reveal the practical significance of different theoretical positions.
Keywords: Criminal Law